The Physics of Ferromagnetism - Miyazaki, Terunobu; Jin, Hanmin; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book covers both basic physics of ferromagnetism such as magnetic moment, exchange coupling, magnetic anisotropy and recent progress in advanced ferromagnetic materials. Special interests are focused on NdFeB permanent magnets and the materials studied in the field of spintronics. In the latter, development of tunnel magnetoresistance effect through so called giant magnetoresistance effect is explained.
Part I: Foundation of magnetism -- Basis of magnetism -- Magnetism of atoms -- Magnetism of solids -- Exchange interaction -- Magnetic anisotropy -- Magnetostrictive effects -- Magnetic domain -- Micromagnetism -- Part II: Magnetic materials -- Soft magnetism -- Hard magnetism -- Part III: Spintronics -- Magnetoresistance effect -- Tunnel magnetoresistance effect -- Magnetoresistive random access memory (MRAM) -- Technologies that accompany the development of spintronics devices.
Keywords: Physics; Magnetism; Engineering; Materials; Physics; Magnetism, Magnetic Materials; Metallic Materials; Structural Materials; Nanotechnology and Microengineering